Public Relations Practice in Issue Management of Inclusive Schools - Iva Fikrani Deslia (CHANNEL: Jurnal Komunikasi, 2021)
The communications management aspect of inclusive schools is essential because the main constraints of inclusive schools and children with special needs (ABK) to advance and access education are not in their disability or impairment but on public acceptance. This research is motivated by the negative issues faced by inclusive schools. Negative assumptions against inclusive schools and children with special needs are challenges for inclusive schools. Therefore, inclusive schools need issue management. This research aims to know the communications management in inclusive school management conducted by SD Tumbuh 1 Yogyakarta. The approach used in this research is qualitative with the case study method. Data collection techniques used are in-depth interviews, observation, and documentation. The research result shows that SD Tumbuh 1 conducted issue management in five stages: problem identification, issue analysis, issue change strategy options, issue actions programming, and result evaluation.  Society has given a positive response because of the various programs that have been organized to handle the issue. The inclusive aspect implemented by SD Tumbuh 1 can be portrayed as an added value for the school.  As a recommendation, communication with the public of inclusive schools must be built continuously, consistently, and involving various parties. Communication acts that are persuasive and educative are also needed to construct positive opinions on inclusive schools. The use of mass media and social media also still needs to be optimized. For further research, because this study captured the school’s issue management, there is an opportunity to research issue management from the public.